A geophysical approach to the archaeological excavation of Plasi Marathon (Attika, Greece) - Souglakos, N.; Alexopoulos, J.D.; Voulgaris, N.; Dilalos, S.; Mitsika, G.S.; Petrakis, M.; Vavouranakis, G.; Valavanis, P.; Papadatos, Y. (Bulletin of the Geological Society of Greece, 2019)
Many researchers have presented that ground penetrating radar (GPR) is a subsurface survey method indicated to acquire important preliminary information in various geological subsurface investigations, but also in archaeological and cultural heritage studies (Conyers, 2016). GPR stands out among the geophysical methods applied in archaeology, given the fact that it is a non-destructive practical field technique. GPR results can be presented as bi-dimensional profiles (2D) and three-dimension images (3D), in the form of block diagrams, fence-diagrams and volume/depth-slices. Especially the amplitude maps (e.g., depth-slices maps) allow the identification of areas with high or low amplitude of specific deep reflectors. Therefore, they can be used to identify buried targets and their dimensions, allowing the reconstruction of the subsurface in 3D (Porsani et al., 2010).